Effective use of quality function deployment and Kansei engineering for product planning with sensory customer requirements: A plain yogurt case. Issue Volume 30:Issues 4(2018) (2nd October 2018) - Dolgun, Leman Esra; Köksal, Gülser
ABSTRACT: Product planning, as typically the first phase of quality function deployment, involves identifying customer requirements and translating them into technical requirements. Understanding true customer needs and setting targets for customer and technical requirements can be very difficult especially when sensory product characteristics such as taste, odor, and texture are concerned. In this study, effective approaches are developed and implemented for overcoming these difficulties in a plain yogurt case. A customer survey is designed using Kansei words and liking questions. Survey data are analyzed using hypothesis tests and building logistic regression models. Target setting processes are facilitated by optimizing these models.